The Poetics of Visual Cubism: Guillaume Apollinaire on Pablo Picasso - Pamela A. Genova (Studies in 20th & 21st Century Literature, 2003)
Guillaume Apollinaire, one of the most original poets of the early twentieth-century French avant garde, played a crucial role in the enunciation of modernist aesthetics. Through innovative poetic forms, Apollinaire set forth a new aesthetics which underscored the inherent ambiguity of an increasingly turbulent modern context. Apollinaire's interest in the pure dynamism of the contemporary material landscape, and his attraction to the image that explodes with immediate presence, also led him to a natural curiosity in the visual arts. Identifying with the Cubist mosaic style of inclusion, the juxtaposition of reality and imagination, and the simultaneity of spatial and temporal movement, Apollinaire saw modern artists as "singers of a constantly new truth," inventors of a uniquely authentic modern experience. Apollinaire composed verse to honor his favorite painters, but he also wrote critical studies on the visual arts, and he declares that it is in Cubist art that we can discover a truly successful endeavor to come to terms with the upheavals of modernity. In several texts Apollinaire devotes specifically to Picasso, he argues that his canvases contain the most essential aspects of modern art: a new interpretation of light, a genuine understanding of the elusive notion of the "fourth dimension," and an incarnation of the most modern of principles, surprise. Apollinaire's texts on Picasso, examples of his poésie critique, do not remain simply words printed on a page, but are transformed into an extension of the painting he wishes to convey, experimental and unpredictable in discursive tone and poetic style. Through these texts, Apollinaire moves beyond the parameters of a journalistic style of criticism, as his pieces on Picasso take on a chameleon-like power of movement, engendering unique forms of an avant-garde improvisation, the painting of prose poetry.
Keywords: Guillaume Apollinaire; original; poet; twentieth-century; French avant garde; avant garde; modernist aesthetics; modernist; ambiguity; pure dynamism; visual arts; Cubist mosaic style; cubism; reality; imagination; spatial and temporal movement; authentic; authentic experience; Picasso; modern art; light; fourth dimension; surprise; poésie critique; experimental; unpredictable; prose poetry; painting